Development of human resources In the perspective of the career development of teachers at the State Vocational School in Makassar City - Sudarmi Sudarmi; Syamsul Sunusi; Agus Syam (Jurnal Ad'ministrare, 2019)
This research was conducted to answer the problem of "how to develop the career of state vocational school teachers in Makassar City". Thus, this study aims to determine the career development of teachers in the State Vocational School in Makassar City. This research is a descriptive study that provides an overview of Career Development of Vocational School Teachers in Makassar City, with a total sample of 73 people. Data collection techniques used are, observation and questionnaire. Data analysis used is; descriptive statistical analysis. The results of the study showed that the career development of the teachers of State Vocational Schools in Makassar City was still in the less category. While supporting factors, namely; 1) teacher's pedagogic competence, 2) the implementation of duties and responsibilities by the teacher professionally, 3) the teacher focuses on carrying out duties in carrying out the duties and responsibilities, 4) the existence of Subject Teachers' Consultation (MGMP), and 5) availability of adequate facilities and infrastructure . While the inhibiting factors of teacher career development are; 1) MGMP is not routinely carried out 2) MGMP funds are not prepared by the government, 3) unclear workload between functional tasks and administrative duties, 4) absence of regulations, especially legal issues that can protect teachers, 5) promotion does not automatically, 6) school management that is not good, 7) the absence of reward commensurate with teacher performance, and 8) inadequate facilities and infrastructure.